PENGARUH ADVERTISING, BRAND IMAGE DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN PADA LJ HOOKER GRAND BATAM - kasno, Kasno; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2021)
Today's growth in the property business is growing rapidly. This will have an impact on the emergence of rapid competition between companies in the property sector. Companies are trying to create services that are most suitable for their customers who can do business in this era of global competition, this is also a big challenge for every company to be more advanced. The purpose of this study was to determine the effect of advertising, brand image and sales promotion on purchasing decisions at LJ Hooker Grand Batam. The sampling technique in this study is a quantitative researcher with a population of 200 customers, the number of samples taken is 115 respondents. Data obtained by distributing questionnaires to LJ Hooker Grand Batam customers. Data analysis was performed using multiple linear regression analysis. The data quality test in this study used the validity and reliability tests, the classic assumption tests in this study used the normality test, the multicollinearity test and heteroscedasticity test and the effect test used multiple linear regression analysis and analysis of the coefficient of determination (R2), while the hypothesis testing in this study using the t test and the F test using the SPSS version 25 software program